Development of Competency Based Assessment Model on Job Performance in Family Welfare Education Apprenticeship - Jubaedah, Yoyoh; Rohaeni, Neni; Rinekasari, Nenden R. (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2017)
The assessment tool to evaluate learner performance on the apprenticeship is variety. Therefore, we were need a standardized assessment tool. This study was attempt to develop a competency based assessment model on job performance in apprentice of the family welfare education. Problem solving was conducted using research and development approach, through stages of: (1) a study introduction, (2) a development model, and (3) a validation model. The research subjects are internal and external tutors, also a learner intern. Data collection was carried out by interviews, observation, survey and expert judgment. The results showed that the planning, the instrument and the implementation of the assessment was the development of competency based assessment model on job performance in family welfare education apprenticeship. Planning assessment was consisting of components of the purpose, job performance, and assessment methods. An instrument assessment was use a test of performance in the form of assessment rubrics. The implementation of the assessment was covering a preparation, collecting, judging, deciding, and moderation stage. From the validation model through the expert judgment, it turns out that assessment model was already developed feasible to implement on job performance assessment in family welfare education apprenticeship